How do I: Evaluate the safety and legitimacy of unproven cellular therapies?. Issue 3 (10th February 2022) - Guleria, Indira; de Los Angeles Muñiz, Maria; Wilgo, Matthew; Bapat, Asawari; Cui, Wanxing; Hsu, Yen‐Michael Sheng; Jeyaraman, Madhan; Muthu, Sathish; Rodriguez, Federico; Fesnak, Andrew; Celluzzi, Christina; Sesok‐Pizzini, Deborah; et al.
Abstract: Background: Unproven cellular therapies are being offered to patients for a variety of conditions and diseases for which other treatments have failed. The use of untested cellular therapies is a worldwide problem. Practitioners (e.g., physicians, scientists, QA/QI facility managers, and policy advocates) are perhaps unaware of the risks involved with such therapies. Therefore, a critical need exists to bring attention to the potential limitations and adverse effects of these therapies to inform and limit misinformation. Study Design and Methods: We describe the extent of the unproven cellular therapy problem through a search of scientific literature and social media coverage. We also describe the regulatory framework that can be used by the practitioner to review and evaluate both proven and unproven cellular therapies. Results: We report on the current state of unproven cellular therapies across the globe. A workflow to facilitate an understanding of the regulatory processes involved in the approval of cellular therapies is provided as well as a list of warnings required by regulatory agencies on various products. It is hoped that this article will serve as a tool kit to educate the practitioner on navigating the field of unproven cellular therapy products. Discussion: Increasing awareness of the issues associated with unproven therapies through education is important to help in reducing misinformation and risks to patients.